Drill Methods for Enhancing Reading Skills in the Era of Digital Disruption: A Systematic Literature Review - Yudha, Vidia Pandji; Jamaludin, Ujang; Hilaliyah, Tatu (FKIP Universitas Lampung, 2025)
Drill Methods for Enhancing Reading Skills in the Era of Digital Disruption: A Systematic Literature Review. Objectives: This research aims to systematically review various studies on the use of the drill method in enhancing reading skills, particularly in the context of the digital era. Methods: This research employs a systematic literature review using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) report guidelines. The articles selected for review meet the following criteria: (1) relevance to the topic, (2) peer-reviewed research publications, (3) published between 2010 and 2025, and (4) written in an international language. Data was collected by searching references in academic journal databases, such as ERIC, Google Scholar, Scopus and Web of Science. Findings: The results highlight several key points: (1) The drill method proves effective in improving reading skills by facilitating faster word recognition and enhancing memory retention; (2) It contributes to better reading speed, comprehension, and phonetic abilities; (3) Different types of drills, such as traditional, repetition-based, and incremental, can be tailored to specific learning needs; (4) The impact of drills is more significant when integrated with innovative teaching strategies; and (5) Digital technology enhances the effectiveness of drills, making learning experiences more interactive, adaptive, and engaging. Conclusion: This study affirms that the drill method significantly supports reading skill development, especially when combined with modern instructional approaches and digital tools. The results of this study are expected to encourage the integration of drill methods with digital technology and innovative strategies to improve the effectiveness of reading learning in the digital era. Keywords: drill method, reading skills, systematic literature review.